Protective Effect of Curcumin on D-Galactose-Induced Senescence and Oxidative Stress in LLC-PK1 and HK-2 Cells - Semiramis Stephania García-Trejo; Tania Gómez-Sierra; Dianelena Eugenio-Pérez; Omar Noel Medina-Campos; José Pedraza-Chaverri (MDPI AG, 2024)
D-galactose has been widely used as an inducer of cellular senescence and pathophysiological processes related to aging because it induces oxidative stress. On the other hand, the consumption of antioxidants such as curcumin can be an effective strategy to prevent phenotypes related to the enhanced production of reactive oxygen species (ROS), such as aging and senescence. This study aimed to evaluate the potential protective effect of curcumin on senescence and oxidative stress and endoplasmic reticulum stress induced by D-galactose treatment in Lilly Laboratories Culture-Porcine Kidney 1 (LLC-PK1) and human kidney 2 (HK-2) proximal tubule cell lines from pig and human, respectively. For senescence induction, cells were treated with 300 mM D-galactose for 120 h and, to evaluate the protective effect of the antioxidant, cells were treated with 5 µM curcumin for 24 h and subsequently treated with curcumin + D-galactose for 120 h. In LLC-PK1 cells, curcumin treatment decreased by 20% the number of cells positive for senescence-associated (SA)-β-D-galactosidase staining and by 25% the expression of 8-hydroxy-2'-deoxyguanosine (8-OHdG) and increased by 40% lamin B1 expression. In HK-2 cells, curcumin treatment increased by 60% the expression of proliferating cell nuclear antigen (PCNA, 50% Klotho levels, and 175% catalase activity. In both cell lines, this antioxidant decreased the production of ROS (20% decrease for LLC-PK1 and 10 to 20% for HK-2). These data suggest that curcumin treatment has a moderate protective effect on D-galactose-induced senescence in LLC-PK1 and HK-2 cells.